IDENTIFICATION OF FRACTIONAL ORDER SYSTEMS WITH NONZERO INITIAL CONDITIONS AND CORRUPTED BY NONZERO-MEAN NOISES - Shuen , W.; Yao , L.; Yinggan , T. (EurasianUnionScientists, 2020)
Most methods in the literature for fractional order systems identification ignore the initial condition and assume the measurement noise is zero mean, which may lead to incorrect estimation. In this paper, the problem of accurate parameter estimation of fractional order system with nonzero initial conditions and corrupted by nonzeromean Gaussian noises is investigated. The initial conditions along with the mean of noise are treated as extra parameters of the system. The parameter, the differential orders and the extra parameters are simultaneously estimated via minimizing the error between the output of actual fractional order system and that of the identified system. In order to reduce the computation complexity of fractional derivatives of input and output signals, the operation matrix of block pulse function is adopted to convert the fractional order system to an algebraic one. Experimental results demonstrates the effectiveness of the proposed method